A lung specific escape of intravascular metastatic breast cancer cells from cytotoxic T cell killing - Kizner, Marina; Levi, Nehora; Sochen, Carmel; Ryvkin, Julia; Regev, Ofer; Zarbock, Alexander; Eisenbach, Lea; Biton, Moshe; Alon, Ronen (Frontiers in Immunology, 2026)
The lungs are a major organ of cancer metastasis. Despite advances in the usage of tumor- specific cytotoxic T cells (CTLs) with potent killing activity (i.e., tumor infiltrating T cells, TILs) for killing of primary tumors, how these T cells encounter and kill metastatic lesions at remote organs is still poorly understood. In the present study we compared the ability of potent neoantigen specific CTLs to kill two types of cancer cells that share the same neoantigen and generate distinct metastatic lesions in the lungs of immunocompetent recipient mice. We have used ovalbumin (OVA) as a neoantigen model and found that the OVA-specific OT-I transgenic CD8 CTLs, when intravenously introduced, readily eliminated primary tumors of OVA-expressing breast cancer E0771 cells. Nevertheless, similar OT-I CTLs failed to clear OVA-expressing breast cancer E0771 cells that colonized the lungs. In contrast, similar intravenously introduced OT-I CTLs efficiently eliminated lung metastatic OVA-expressing B16 melanoma cells, ruling out that the intravenous CTLs were exhausted upon entering the lungs. Three-dimensional (3D) imaging of whole lungs revealed that in both experimental and spontaneous metastasis models, the OVA E0771 cells survived inside lung blood vessels but did not recruit circulating OT-I CTLs to their vicinity. Furthermore, canonical vascular adhesion molecules recognized by the CTLs like ICAM-1 and VCAM-1 were not upregulated nearby the lung-residing intravascular E0771 cells as a potential means to recruit lung circulating CTLs to the vicinity of the intravascular tumor cells. Strikingly, the lung residing OVA-expressing E0771 cells lost expression of their OT-I specific OVA-derived SIINFEKL-H-2Kb pMHC complexes while retaining MHC-I expression. This loss was accompanied by a lung-specific transcriptional reduction of key regulators of MHC-I presentation. A temporal loading of OVA-derived SIINFEKL-H-2Kb pMHC complexes on E0771 cells did not result, however, in cancer cell killing inside the lungs. Nevertheless, direct and stable SIINFEKL peptide presentation on these cells overcame their lung specific escape from OT-I mediated killing. Our study is a first indication that subsets of cancer cells that reside in the lungs rapidly downregulate the expression of neoantigen derived peptide MHC-I complexes and thereby evade killing by intravenously introduced tumor antigen-specific CTLs.